Pengaruh Model Problem Based Learnig Terhadap Kemampuan Berpikir Kreatif Siswa Pada Materi Statistika Kelas VIII di SMP PGRI 1 Palembang - Najla, Indhika Aulya; Retta, Allen Marga; Ningsih, Yunika Lestaria (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to determine whether or not there is an influence of the Problem Based Learning (PBL) model on creative thinking skills in statistical material for class VIII at SMP PGRI 1 Palembang. The research method used is True Experiment with the form of Posttest-Only Control Design. This research was conducted at SMP PGRI 1 Palembang, Palembang City and it was implemented in the Seven Semester of the 2023/2024 Academic Year. The population used was all classes VIII with a sample of class VIII.1 as many as 31 students and VIII.2 as many as 31 students, obtained using the Random Sampling data analysis technique. The data collection used was a creative thinking ability test and the data analysis test using the Independent Sample T-Test based on the results of the study and data analysis showed that there was an influence of the PBL model on creative thinking skills in statistical material for class VIII at SMP PGRI 1 Palembang.